The Effect of Transformational Leadership and Organizational Culture on Organizational Commitment Role of Mediation Empowerment Military of Kodim 0510/Tigaraksa, Tangerang - Wira Satria Dawy; Corry Yohana; Agus Widodo (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of transformational leadership and organizational culture on organizational commitment by examining the mediation of empowering members at Kodim 0510/ Tigaraksa, Tangerang Regency. In total, 252 members completed an online questionnaire that assessed transformational leadership, organizational culture, empowerment, and organizational commitment. The organizational commitment model was tested using a structural equation model. The results showed that empowerment mediates the relationship between transformational leadership and organizational commitment, it also mediates the relationship between organizational culture and organizational commitment.